Effects of carbohydrate supplementation on performance and carbohydrate oxidiation during overreaching - Halson, S.; Lancaster, G.; Achten, J.; Gleeson, M.; Jeukendrup, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Athletes often employ an increase in training intensity in a bid to improve performance, however if this is combined with inadequate recovery overreaching (OR) or overtraining (OT) may result. Whilst training stress and a disturbance in homeostasis is generally accepted to lead to OR and OT, the underlying mechanism remains elusive (1). It is perceivable that the fatigue and reduced performance associated with OR and OT may be partly attributable to muscle glycogen depletion. The aim of this study was to examine the metabolic effects of carbohydrate supplementation on cycling performance before a period of OR, immediately after OR and following recovery. Methods Six endurance-trained cyclists completed 4 weeks of training on two occasions, once with high carbohydrate supplementation (H-CHO) before, during and after training and once with low CHO (L-CHO). Each 4 week period included one week of normal training, one week of intensified training (IT) and 2 weeks of recovery (R). Before IT, after IT and after R each subject performed an endurance capacity test (EC) at 62.5±1.1% of peak power output. During EC a primed continuous dose of [6,6-2H2]glucose was given and blood samples were collected for measurement of plasma glucose enrichment, adrenaline, cortisol, glucose, lactate, free fatty acids (FFA), tryglycerides and glycerol. Oxygen consumption, heart rate and RPE were also measured during EC. Dietary intake was recorded during IT and both subjects and researchers were blinded to the treatment. Mood state was also assessed. Results Mean daily intake during IT was significantly higher in the H-CHO trial (H-CHO: 16.5±0.9MJ; L-CHO: 13.0±1.0MJ and CHO intake was also greater in this trial (H-CHO: 9.4±1.0g/kgBW/day; L-CHO: 6.4±0.5g/kgBW/day). Endurance capacity significantly declined in both trials after IT, however the decline in performance was attenuated during the H-CHO trial (H-CHO: 17±3%; L-CHO: 26±7%). Following R, performance was increased by 11± 4% above baseline in the H-CHO trial, whereas performance remained 13±11% below baseline during L-CHO. Mood disturbance measured by the POMS was increased in both trials, however it was increased to a greater extent in the L-CHO trial and remained elevated after R (See Table 1). Submaximal RPE was significantly elevated in both trials after IT, however if was higher in the L-CHO trail than the H-CHO trial and remained elevated in this trial during R. A trial X diet effect was observed for submaximal plasma concentrations of cortisol, adrenaline and prolactin with greater reductions in these stress hormones in L-CHO than H-CHO after IT. Rates of appearance and disappearance of [6,6-2H2]glucose were unchanged throughout the study period. Whole-body CHO oxidation was significantly decreased in both trials after IT (p=0.01) and concomitantly fat oxidation increased in both trials (p=0.01). RER, plasma glucose, lactate and tryglycerides were lower after IT in both trials and glycerol and FFA concentrations were higher after IT in both trials. Discussion/Conclusion The provision of CHO before, during and after training did not prevent the development of overreaching, however, it attenuated the decrease in performance and the increase in mood disturbance experienced by the subjects. Although large changes in whole-body substrate oxidation were observed, mechanisms other than glycogen depletion play a role in the development of overreaching. The decrease in plasma hormone concentrations to standardised exercise suggests that the hypothalamic- pituitary adrenal axis may be desensitised during overreaching.